Prediabetes awareness among Southeastern European physicians. Issue 3 (28th September 2017) - Kokic, Visnja; Kokic, Slaven; Krnic, Mladen; Petric, Marin; Liberati, Ana Marija; Simac, Petra; Milenkovic, Tatjana; Capkun, Vesna; Rahelic, Dario; Blaslov, Kristina
Abstract: Aims/Introduction: Prediabetes (PD) represents a transitional state where the glucose levels are higher than normal, but not enough for diabetes mellitus diagnosis. As there is a growing number of the population with PD, its early detection and treatment could prevent the development of diabetes mellitus and its complications. We aimed to assess the overall knowledge of PD among medical professionals of different varieties. Materials and Methods: A questionnaire‐based study addressing PD and type 2 diabetes mellitus knowledge among Southeastern European general practitioners, postgraduates, physicians and superior specialists was carried out. Results: A total of 397 physicians completed the questionnaire. The total rate of correct answers from diabetologists, non‐diabetologist internists, residents and general practitioners was 69, 56.1, 54 and 53%, respectively. Questions related to the PD definition achieved a total of 46.6% correct answers. Correct responses considering the numerical definition of impaired fasting glucose and impaired glucose tolerance were 46.3 and 46.8%, respectively. Younger physicians had better knowledge of numerical values regarding PD and type 2 diabetes mellitus criteria ( P < 0.001). Conclusions: The present results show that overall knowledge of PD is poor among Southeastern European physicians, which necessitates adequate educational programs on PD in this region. Abstract : Prediabetes (PD) represents a transitional state where the glucose levels are higher than normal but not significant enough to be diagnosed with diabetes mellitus (DM). A questionnaire based study addressing knowledge on PD and type 2 DM was conducted among South‐Eastern Europe practitioners, and results indicated insufficient general knowledge on PD with only 55.5% of total correct answers. Prediabetes overall knowledge is poor among South‐Eastern physicians which might require adequate educational programs on PD in this region.